2011
DOI: 10.1016/j.juro.2011.03.130
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Trends for Stage I Renal Cell Carcinoma

Abstract: Purpose: Renal cell carcinoma is increasingly diagnosed at stage I, and among stage I cases mean tumor size has been decreasing. Previous reports suggest that nephron sparing surgery is underused for small renal cell carcinomas. We determined updated, population based treatment trends for stage I renal cell carcinoma. Materials and Methods:The National Cancer Data Base, which captures approximately 70% of all cancer diagnoses in the United States, was queried for renal cell carcinoma in adults diagnosed betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 25 publications
5
49
2
3
Order By: Relevance
“…However, patterns of utilisation of PN for pT1a tumours similar to those reported here have been seen in USA population-based data, although some of these studies have used less contemporary population samples [24,25]. Whilst more recent USA data from the Surveillance Epidemiology and End Results Program (SEER) and the National Cancer Database have shown increasing use of nephron-preserving surgery with PN and ablative techniques, significant underutilisation still exists according to the investigators [31,32]. Interestingly, SEER data from 2006 showed PN to represent 45% of kidney surgery for renal tumours of Յ4cm, a figure slightly higher than seen in the present population [32].…”
Section: Discussionsupporting
confidence: 58%
“…However, patterns of utilisation of PN for pT1a tumours similar to those reported here have been seen in USA population-based data, although some of these studies have used less contemporary population samples [24,25]. Whilst more recent USA data from the Surveillance Epidemiology and End Results Program (SEER) and the National Cancer Database have shown increasing use of nephron-preserving surgery with PN and ablative techniques, significant underutilisation still exists according to the investigators [31,32]. Interestingly, SEER data from 2006 showed PN to represent 45% of kidney surgery for renal tumours of Յ4cm, a figure slightly higher than seen in the present population [32].…”
Section: Discussionsupporting
confidence: 58%
“…20 Finally, many patients simply do not have access to PN, for reasons that could pertain to traveling time, inability to be treated at a hospital that offers PN, insurance, racial disparity or socioeconomic status. [21][22][23][24][25] Indeed, in analyses focusing on characteristics most associated with PN treatment, the present results showed that younger individuals and males were more likely to be treated with PN than their older and female counterparts. Interestingly, the present results also showed that persons of black race were more likely to be treated with the nephron-sparing approach relative to whites, contrary to results of previous reports that suggested a treatment disparity for blacks.…”
Section: 18supporting
confidence: 44%
“…1 Concomitantly, partial nephrectomy has been increasingly recommended over radical nephrectomy for T1 renal cancers. 2 Advantages of nephron-sparing procedures included improved renal functional outcomes without compromising the oncologic safety.…”
Section: Introductionmentioning
confidence: 99%